IMPLEMENTASI SISTEM INFORMASI DATA NILAI SISWA BERBASIS WEB PADA SMK NEGERI 1 NGULING - Endang Widia Astuti (STMIK YADIKA BANGIL, 2019)
State Vocational School 1 Nguling is one of the organizations in which there are teaching and learning activities which are under the responsibility of a school principal. All activities that take place in a school cannot be monitored in its entirety without proper organization. For this reason, the implementation of a web-based student value data information system is an alternative method of overcoming existing problems. By utilizing the sophistication of existing information technology, efficiency in the process of inputting student grades will be increasingly met. One of the information technologies that can be applied is internet technology, by utilizing internet technology, the process of inputing student grades can be done online. in addition, with this application system, students can easily access information about the value of their learning outcomes by using the facilities already provided. That way the nuances of IT will be reflected even though the institution is located ina rural area Keywords: Value data information system